Konsep Teologi Pembebasan Dalam Islam Persepektif Asghar Ali Engineer - Agustiana (Program Studi Aqidah dan Filsafat Islam STISA Ash-Shofa Tasikmalaya, 2025)
Asghar Ali Engineer is a thinker and activist known for his contributions in the field of Liberation Theology, particularly in relation to social justice and liberation for marginalized groups. Liberation theology, according to Engineer, focuses on efforts to liberate humanity from various forms of oppression, whether social, economic, or political. In this perspective, Islam is not only understood as a ritual religion, but as a force that promotes social justice and empowerment for the oppressed. Engineer emphasized the importance of critical interpretation of sacred texts, which can raise awareness of injustice and promote social change. He argued that Islam, with its teachings emphasizing justice, should be understood as a religion that supports the struggle against all forms of inequality and oppression. Overall, the concept of Liberation Theology developed by Asghar Ali Engineer is an attempt to combine spiritual understanding with concrete social action. He suggests that Muslims should be committed to structural changes that can provide justice for all humanity, especially for those who have been marginalized in society.